2019
DOI: 10.1080/01904167.2018.1549675
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant related biochemical traits are significant indices in triticale grain yield under drought stress condition

Abstract: Two separate experiments, one as drought stress condition and the other one as the normal irrigation condition based on randomized complete block design (RCBD) with three replications were implemented to examine 20 triticale (Triticoseclae wittamack X) genotypes of which 19 genotypes have recently been generated by crossing different parent lines and the other one was Javaniloo, common cultivar. Based on the results of different statistical techniques and comparing relationships among traits for normal irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 54 publications
2
7
0
2
Order By: Relevance
“…In accordance with our results regarding the importance of SOD activity, the relationship of biochemical features and grain yield of triticale was modeled in the study of Saed-Moucheshi [ 45 ], without estimation of their heritability and other genotypic parameters, and it showed that showed that MDH, proline contents and SOD were the important features with significant impacts on triticale grin yield. Similarly, Riasat et al [ 43 ] nominated SOD activity as the most appropriate trait to obtain higher tolerant triticale genotypes. In addition, there are several studies on different crops that are in concordance with our results regarding the importance of biochemical features as the selection criteria [ 1 , 33 , 44 , 54 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our results regarding the importance of SOD activity, the relationship of biochemical features and grain yield of triticale was modeled in the study of Saed-Moucheshi [ 45 ], without estimation of their heritability and other genotypic parameters, and it showed that showed that MDH, proline contents and SOD were the important features with significant impacts on triticale grin yield. Similarly, Riasat et al [ 43 ] nominated SOD activity as the most appropriate trait to obtain higher tolerant triticale genotypes. In addition, there are several studies on different crops that are in concordance with our results regarding the importance of biochemical features as the selection criteria [ 1 , 33 , 44 , 54 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative traits related to plant senescence have already been mapped for e.g., sorghum, maize, rice, wheat, potato, or cowpea [38][39][40][41][42][43]. Drought-induced plant senescence markedly limits crop productivity [44]. This is the first study that presents the results of QTL mapping in triticale, where drought-induced senescence may be controlled by wheat or/and rye genome [27].…”
Section: Resultsmentioning
confidence: 97%
“…In accordance with our results regarding the importance of SOD activity, the relationship of biochemical features and grain yield of triticale was modeled in the study of Saed-Moucheshi (2018), without estimation of their heritability and other genotypic parameters, and it showed that showed that MDH, proline contents and SOD were important features with significant impacts on triticale grin yield. Similarly, Riasat et al (2019) nominated SOD activity as the most appropriate trait to obtain high tolerant triticale genotypes. In addition, there are several studies on different crops that are in concordance with our results regarding the importance of biochemical features as the selection criteria (Riasat et al, 2020;Tabarzad et al, 2017;Vosough et al, 2019;Zahedi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%